The facilitating and hindering factors in the deployment of digital services of occupational health care - Karppi, Marion; Koroma, Johanna (Finnish Journal of eHealth and eWelfare, 2021)
Technological development enables the production of achievable and customer-centred preventive occupational health services for employees working in multiple locations. Occupational health care has also encountered the need for digital health care services due to the expansion of mobile work, as the companies and work are more digitalized and internationalized. This research, conducted in three different occupational health care organizations in 2016-2018, aims to explore the features affecting the development of preventive digital services in occupational health care. The research comprised of exploring the current situation of preventive services in occupational health care and the co-creation, piloting, and evaluation of preventive digital services. The research utilized the realistic evaluation method. The results describe the functional environments of occupational health services and the facilitating and hindering factors found in the environments during the piloting process. The results can be utilized in occupational health care services as they develop and implement new digital services.